The 7‐year cumulative incidence of cornea guttata and morphological changes in the corneal endothelium in the Reykjavik Eye Study. (17th February 2012) - Zoega, Gunnar M.; Arnarsson, Arsaell; Sasaki, Hiroshi; Söderberg, Per G.; Jonasson, Fridbert
Abstract: Purpose: To examine the corneal endothelium and establish the 7‐year cumulative incidence of cornea guttata (CG). Methods: Population‐based prospective cohort study with 573 participants (third wave of the Reykjavik Eye Study (RES) in 2008). Four hundred and thirty‐seven subjects had either right or left eyes available for analysis after excluding confounding eye conditions. The baseline for eyes at risk for developing CG is the second wave of the RES in 2001. Participants underwent specular microscopy and a standardized eye examination. Results: The cumulative 7‐year incidence of CG in either eye was estimated as a 95% confidence interval for the expected value for both genders combined (15–23%), for males (8–18%) and for females (19–29%). In right eye only, the 7‐year cumulative incidence for both genders combined was estimated to be 6–11%. For genders combined and for males only, the data indicated no correlation between 7‐year cumulated incidence and age at baseline. In women, however, the change of 7‐year incidence for CG in at least one eye appeared to be correlated to age at baseline. Reduction of endothelial cell density for corneas with CG at baseline was found [CI (0.95)−132 ± 94]. Conclusion: The cumulative 7‐year incidence of primary central CG for a middle‐aged and older Caucasian population without history of potentially confounding eye disease has been established. Women tend to have higher incidence if onset occurs at middle age. If CG is present, the cell density and the cell size variation decrease within a 7‐year period.